2022
DOI: 10.3390/molecules27144500
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antimicrobial and Antioxidant Rich Pomegranate Peel Based Edible Coatings on Quality and Functional Properties of Chicken Nuggets

Abstract: The current study evaluated the effect of pomegranate peel-based edible coating on chicken nuggets in order to develop a functional and safe product, high in nutritional value. For this purpose, 2,2-diphenyl-1-picrylhydrazyl (DPPH) and total phenolic content (TPC) assays were performed to check the potential antioxidant activity of chicken nuggets; microbial control, including total aerobic count and coliforms population, was performed for quality and safety purposes; and thiobarbituric acid reactive substance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Since it is found to be rich in a number of phytochemicals, this fruit crop has had broad industrial applications in food-and therapeutic-related industries [20]. Additionally, pomegranate peel (Pp) is considered one of the agro-wastes with wide availability, covering around 40-50% of the total weight of the fruit [21]. Further, Pp contains potential reactive oxygen species (ROS) owing to being enriched with bioactive compounds, namely polyphenols with gallic acid and tannins, which amount toaround ~25-28% of the total portion [22].…”
Section: Introductionmentioning
confidence: 99%
“…Since it is found to be rich in a number of phytochemicals, this fruit crop has had broad industrial applications in food-and therapeutic-related industries [20]. Additionally, pomegranate peel (Pp) is considered one of the agro-wastes with wide availability, covering around 40-50% of the total weight of the fruit [21]. Further, Pp contains potential reactive oxygen species (ROS) owing to being enriched with bioactive compounds, namely polyphenols with gallic acid and tannins, which amount toaround ~25-28% of the total portion [22].…”
Section: Introductionmentioning
confidence: 99%
“…The liver has a high antioxidant potential that leads to oxidative stability, as a study on porcine liver-extracted hydrolysates showed a high scavenging potential of free radicals ( Verma et al, 2017 ). Literature also suggests using pomegranate peel-based coatings ( Bashir et al, 2022 ) and frozen white cauliflower ( El-Anany et al, 2020 ) to boost antioxidant activity in chicken nuggets. This antioxidant potential enhancement by the liver can be seen in the chicken nuggets supplemented with liver.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of various edible coatings with antimicrobial agents on the shelf life of food products were previously reported in the literature. For example, Bashir et al [ 59 ] documented a reduction of the microbial population of the coated samples of chicken nuggets during storage with the increase of the coating solution. According to their findings, the total aerobic count was affected significantly by the coating formulations and the storage time.…”
Section: Resultsmentioning
confidence: 99%